Film directing cinematic motion a workshop for stating scenes - Katz, Steven D. (Michael Wiese Production Book, 1992)
Los temas principales son: Staging the process, staging the director, staging the production manager, staging the workshop, basic choreography, blocking in confined spaces
Incluye bibliografía
Keywords: Audiovisual; Cine - Director